Integrating progressive muscle relaxation and guided imagery based on adaptation model for pain management in ovarian cancer: A nursing case study - KK, Indra Frana Jaya; Nainggolan, Sutrisari Sabrina; Ningsih, Deasy Kurnia; Cahya, Febriani; Amalah, Frita Anesia; Rahayu, Rita Puji; Maharani, Shinta (Lentera Perawat, 2026)
Background: Ovarian cancer frequently causes severe pain and psychological distress that negatively affect patients’ physiological and psychological well-being. Effective pain management in oncology nursing requires comprehensive strategies that combine pharmacological treatment with supportive non-pharmacological interventions. However, evidence regarding the integration of these techniques within the Roy Adaptation Model for pain management in ovarian cancer patients remains limited. Objective: This study aimed to analyze the effectiveness of integrating Progressive Muscle Relaxation and Guided Imagery based on the Roy Adaptation Model to reduce pain and anxiety in patients with ovarian cancer through a nursing case study. Methods: This study employed a descriptive case study design conducted in the Paviliun Cemara ward at RSUD Siti Fatimah, South Sumatra Province. Three ovarian cancer patients experiencing acute pain were selected using purposive sampling based on predefined inclusion criteria. Data collection was carried out through interviews, physical examination, observation, and measurement of pain and anxiety levels using the Numeric Rating Scale (NRS) and Hamilton Anxiety Rating Scale (HARS). The intervention consisted of Progressive Muscle Relaxation and Guided Imagery sessions administered twice daily for three consecutive days. Data were analyzed descriptively by comparing changes in pain and anxiety scores before and after the intervention. Results: The findings showed a consistent reduction in pain intensity and anxiety levels among all participants after the intervention. Patient 1 experienced a decrease in pain from NRS 7 to 3 and anxiety from HARS 24 to 12. Patient 2 showed a reduction in pain from NRS 8 to 0 and anxiety from HARS 18 to 8. Patient 3 demonstrated improvement with pain decreasing from NRS 8 to 2 and anxiety from HARS 25 to 10. Improvements were also observed in physiological parameters and patient comfort levels, indicating positive adaptive responses to the intervention. Conclusion: The integration of Progressive Muscle Relaxation and Guided Imagery based on the Roy Adaptation Model demonstrated beneficial effects in reducing pain and anxiety among patients with ovarian cancer. These findings suggest that relaxation-based nursing interventions may serve as effective complementary strategies in oncology pain management and support patient adaptation to illness.